PHYSICAL ACTIVITY IN DEPRESSION MANAGEMENT: MECHANISMS, CLINICAL IMPLICATIONS, AND EXERCISE PRESCRIPTION - A NARRATIVE REVIEW - Katarzyna Zegadło; Katarzyna Jolanta Kuc; Maciej Dobrucki; Krzysztof Brzezicki; Patryk Jakubiak; Aleksandra Cieciora; Mateusz Cieciora; Małgorzata Kawiorska; Julia Surowiec; Wiktoria Ruta Bełcikowska-Skowron (International Journal of Innovative Technologies in Social Science, 2026)
Background: Depression is one of the top contributors to global disability and represents an important public health challenge. Studies show an increasing body of evidence that physical activity might be instrumental in both the prevention of and intervention with depressive disorders. Purpose of the investigation: This narrative review intends to summarize and synthesize current evidence pertaining to the antidepressant effects of physical activity, considering suggested mechanisms, clinical results, and prescription advice of exercise. Material and methodology: The review was compiled after conducting a systematic search of PubMed/MEDLINE, Embase and the Cochrane Library for peer-reviewed publications, stressing high-impact findings published between 2024–2026. Systematic reviews, meta-analyses and well-designed randomized controlled trials (RCTs) with large prospective cohorts were prioritized. Results: The evidence base suggests that there is significant evidence that exercise is associated with decreases in depressive symptoms in varied populations. The proposed mechanisms are changes in monoaminergic neurotransmission, elevation of BDNF, normalization of HPA-axis function, and anti-inflammatory effects. Data support the dose-response relationship, with even small increases in activity positively correlated with mental health improvement. Conclusions: The interventions provided by exercise are beneficial, reasonable and cheap, which is relevant to the prevention and treatment of depression. Studies should focus more on developing specific combinations of exercise recommendations and specific exercise regimens tailored for each patient cohort.